(untitled) (Journal of Bio-Science, 2026)
Aerides crispa Lindl., an epiphytic orchid native to the Western Ghats of India, holds significant ornamental and medicinal values. Unfortunately, several orchid species are recognized as threatened due to habitation loss and lack of inefficient natural propagation. This study aimed to develop a reliable and reproducible in vitro regeneration protocol for A. crispa through asymbiotic seed germination and tissue culture techniques. Green, un-dehisced seedpods harvested 60-63 days after pollination were surface sterilized and inoculated on Murashige and Skoog medium. The highest seed germination (91.67%) occurred on hormone-free MS medium, indicating that exogenous plant growth regulators are not essential for germination. However, 1.0 µM/L BAP significantly enhanced protocorm-like body (PLB) formation (93.33%) and shoot development (90%). Optimal microshoot multiplication (15.52 ± 0.17 shoots/explant) was achieved with 2.0 µM/L BAP + 1.0 µM/L IBA, while maximum shoot elongation occurred at 1.0 µM/L BAP. Rooting was most effective with 4.0 µM/L IBA, producing 93.33% rooting and an average of 4.21 roots/shoot. Among acclimatization substrates, the mixture of garden soil, cocopeat, and charcoal (1:1:1) supported 100% in vivo survival. This study provides a suitable plant propagation approach that might be useful for the conservation of A. crispa, thereby contributing to ex situ conservation of the threatened orchid species and their further commercial cultivation. J. Bio-Sci. 33(1): 79-92, 2025